KONSEP BURDAH DALAM PERSPEKTIF JAMA'AH TABLIGH - Dharmayani Dharmayani; Agus Hermanto; Imam Nur Hidayat; Habib Ismail; Iwannudin Iwannudin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Aurat is a part of the body that must be covered in Islamic teachings. The female genitalia are all parts of the body except the palms and the face. In the concept of Jama'ah Tablighi, burdah is a cloth to cover the face, like a veil. This study aims to examine in depth the concept of burdah which is an effort to cover the genitals in the perspective of the Tablighi Jama'ah. This research is a qualitative type in the form oflibrary research, with a historical-philosophical approach namely studying the concept of burdah historically and philosophically so as to find the correct meaning. The results of this study indicate that in the concept of Jama'ah Tablighi, burdah is an effort to cover the aurat for Muslim women, this is done because women are the ones who become the motivation for da'wah for their husbands, so that all things that are owned by the wife are only for her husband, including the beautiful face. is a source of slander if not guarded. Because the face is a source of slander, the face becomes aurat for women and must be protected by covering it.